South Africa : Detailed Assessment of Implementation on IOSCO Principles-Securities Markets. (IMF Staff Country Reports; Country Report ;, 2010)
South Africa has made substantial progress in addressing the recommendations of the Financial Sector Assessment Program and is continuing to build upon these accomplishments. The Financial Services Board and Department of Trade and Industry both are organizations with the legal authority to regulate and supervise these steps. The South African system of financial services regulation is complex, involving multiple government agencies, several advisory or oversight committees, and several self-regulatory organizations. While all areas of responsibility appear to be covered, there may be gaps in the implementation of duties.